ANALYSIS OF INTERNAL CONTROL SYSTEM AT PT ALBASIA INDO LESTARI PONTIANAK - Ellysa, Ellysa (ABDI EQUATOR, 2021)
Inventory is one of the important assets owned by the company. Since inventory is an asset, a good and appropriate internal controls are required for the control and management of such merchandise to keep the inventory of the bad things that might happen in order for the business to continue operating. The research method used is qualitative method with descriptive analysis by the data gained from in-depth interview with the owner of the business. From the results of research on PT Albasia Indo Lestari, author can conclude that the internal control of quite low. The lack of professional workers has been the main problem of the business. The practice in the business is also still need improvements and the business should also pay attention to its employees’ knowledge and educations so their performances can be improved. There are still many improvements needed so the business can run effective and efficiently.